2021
DOI: 10.1021/acsami.1c11307
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Sunscreen Leakage in Water by Amyloid-like Protein Aggregates

Abstract: A sunscreen offers indispensable skin protection against UV damage and related skin diseases. However, due to the poor interfacial stability of sunscreen coatings on the skin, the synthetic ingredients in sunscreen creams easily fall off and enter aquatic environments, causing large ecological hazards and skin protection failure. Herein, we tackle this issue by introducing amyloid-like protein aggregates into a sunscreen to noticeably enhance the interfacial robustness of sunscreen coatings on the skin. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Our previous work further demonstrated that the phase‐transitioned protein solution (including protein and TCEP) and resultant nanofilm had excellent biocompatibility with mammalian cells and organisms. [ 21,22,43–46 ] In addition, the toxicity evaluation of TCEP on wheat seeds showed that the germination percentage and root length of wheat seeds treated with TCEP solutions at different concentrations (0.0716, 0.716, and 7.16 mg mL −1 ) were at the same level as the untreated wheat seeds (Figure S22, Supporting Information). And the toxicity evaluation of TCEP on wheat leaves also revealed that the height, chlorophyll content, and dry weight of wheat leaves treated with TCEP solutions at different concentrations (0.0716, 0.716, and 7.16 mg mL −1 ) were at the same level as the untreated leaves (Figure S23, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work further demonstrated that the phase‐transitioned protein solution (including protein and TCEP) and resultant nanofilm had excellent biocompatibility with mammalian cells and organisms. [ 21,22,43–46 ] In addition, the toxicity evaluation of TCEP on wheat seeds showed that the germination percentage and root length of wheat seeds treated with TCEP solutions at different concentrations (0.0716, 0.716, and 7.16 mg mL −1 ) were at the same level as the untreated wheat seeds (Figure S22, Supporting Information). And the toxicity evaluation of TCEP on wheat leaves also revealed that the height, chlorophyll content, and dry weight of wheat leaves treated with TCEP solutions at different concentrations (0.0716, 0.716, and 7.16 mg mL −1 ) were at the same level as the untreated leaves (Figure S23, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of chemical sunscreens raises concerns over their potential impact on human health and the environment. Penetration of sunscreens into the skin can cause skin allergies and contribute to coral bleaching [55–57] . Furthermore, the long‐term effects of sunscreen use may result in the increased production of free radicals, which can attack normal cells and contribute to oxidative stress, leading to several diseases and skin aging [28,57] .…”
Section: Resultsmentioning
confidence: 99%
“…[55][56][57] Furthermore, the longterm effects of sunscreen use may result in the increased production of free radicals, which can attack normal cells and contribute to oxidative stress, leading to several diseases and skin aging. [28,57] CDs are novel carbon nanomaterials with widely praiseworthy properties, especially their strong UV absorption and UV protection. [28] As shown in the UV-vis spectra above, all CDs demonstrated excellent UV absorption.…”
Section: Uv Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 64 ] Furthermore, the PTB solution does not pose a threat to humans or nontarget organisms such as mice due to its noncytotoxicity. [ 37 , 76 ] Based on these findings, snails, typical ground pests that have a serious impact on agriculture, were used to evaluate the biological activity of metaldehyde (80%, wettable powder (WP)) in water or as‐prepared PTB solution. Metaldehyde, with the assistance of other attracting agents, would behave the killing function after snails contact with or eat metaldehyde.…”
Section: Resultsmentioning
confidence: 99%